Rainfall Forecasting Model in Nakhon Si Thammarat Province: Case Study Using Time Series Method - Riansut, Warangkhana; Wiriyakulopast, Supamit; Luengaksorn, Natthanon; Photchamnian, Wachirawit (Journal of Science Ladkrabang, 2024)
December 2022. The time series was divided into 2 sets. The first series from January 2012 to December 2021 was used to create the forecasting models using the Box and Jenkins method, the simple seasonal method, Winters’ additive method, and Winters’ multiplicative method. The second series was from January to December 2022 for selecting the forecast model based on the lowest Root Mean Square Error (RMSE). This study found that a model from the Box and Jenkins method, SARIMA (0, 0, 0) (1, 1, 0)12 and no constant term, had the lowest RMSE value.